PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETAMBAK UDANG VANAME EKS PLASMA PT CENTRALPERTIWI BAHARI DESA BRATASENA ADIWARNA - Andini, Cindy Puri; Sayekti, Wuryaningsih Dwi; Prasmatiwi, Fembriarti Erry (Lampung University, 2020)
This research aims to analyze household income, welfare, and factors that influence the household welfare of vaname cultivators ex-plasma PT Centralpertiwi Bahari. Data of this research was collected in Bratasena Adiwarna village in February 2018. Samples in this research were 70 shrimp cultivators households. Determination of samples with simple random sampling. Primary data was obtained by interviewing respondens, while secondary data was obtained from several related institution. Household income consists of shrimp income, nonshrimp, off-farm and nonfarm income. Household welfare level was analyzed by the Sajogyo criteria and poverty line according to BPS Lampung (2017). The factors that influence household welfare was analyzed by binary logistic regression. The research result showed that the average shrimp income in period I, II, and III were Rp7,986,264; Rp13,868,109; and Rp27,334,963; average household income was Rp64,902,569.00 per year, which was obtained from 70 percent of shrimp income, 10 percent of nonshrimp income, 2 percent of off-farm income, and 18 percent of nonfarm income. The household welfare level based on the Sajogyo indicator showed that 37 percent of household were in moderate and 63 percent were in decent living class, while the BPS poverty line shows that all of households were classified as non-poor. The level of household welfare of ex-plasma PT Centralpertiwi Bahari was influenced by household income, and household dependents.Keywords: income, vaname shrimp cultivator, welfare